Pelatihan dan Aplikasi Pembuatan Produk Home Industry Coconut Chips dan Stick Kelor di Desa Kedungsari Kecamatan Kemlagi Kabupaten Mojokerto - Ulfa Rahmawati; Ayu Kumala Sari; Anifa Mustika Prihatini; Anna Yusholluna Alannabi; Mochammad Nur Asik Maulana; Farikhatur Rizkillah; Firda Amalia; Ahmad Saiyet Amiril Mukminin; Bella Novitasari; Yulis Trinanda Setyoningrum; Arindy Alfa Juniarta; Elisa Perdinawati; Frizalsyah Fatkhurozi Wibowo; Hafis Ramadhan; Handika Putra Santoso; Josoa Muda Kurniawan; M. Ridho Nur Hidayah; Moch. Ilham Rahmad Thulloh; Mochamad Hilfi Eka Putra; Unun Nadilah; Vivi Putri Hermalia; Bela Desmita Sari; Bilqis Eka Maharani; Elsa Anggraeni (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2023)
This community service project refers to the UMKM program which includes providing outreach to residents on how to use coconuts and Moringa leaves as a food security innovation. Moringa leaves have the property of lowering blood sugar levels and also have quite high levels of vitamins A and C. And coconuts have the property of reducing inflammation and contain MCT compounds. For this reason, Moringa leaves are processed into Moringa sticks and coconut fruit into chips that are suitable for snacking. Using a hands-on practical approach, this community service project was completed with PKK women in Kedungsari Village. If this business is successful, it will provide benefits to the people of Kedungsari Village at a time when new snack foods are becoming popular and popular in the area because the way they are made is very rare. carried out in society. With its advantages and potential, the people of Kedungsari Village in Mojokerto Regency can gain economic benefits from increasing the use of coconut fruit and Moringa leaves in snacks. This article attempts to develop the original and creative thinking capacity of KKN students while also answering problems related to increasing local economic development through exercises and applications in making goods for the home industry. This activity is considered to have a lot of potential to help the Kedungsari community in building UMKM prospects